Spinel LiMn2O4 nanoparticles fabricated by the flexible soft template/Pichini method as cathode materials for aqueous lithium-ion capacitors with high energy and power density. Issue 25 (21st April 2021) - Xiang, Junyu; Zhang, Pengxue; Lv, Shixian; Ma, Yongjun; Zhao, Qi; Sui, Yan; Ye, Yuncheng; Qin, Chuanli
Abstract : LiMn2 O4 nanoparticles were synthesized by flexible Pichini method with expanded graphite as the soft template to effectively control particle size and agglomeration, contributing to high energy/power densities of its aqueous lithium-ion capacitor. Abstract : Spinel LiMn2 O4 (LMO) with a three-dimensional structure has become one of the cathode materials that has gained the most interest due to its safety, low price and abundant resources. However, the lithium ion transmission is limited by large particle size and particle agglomeration of LMO. Thus, reducing the particle size and agglomeration of LMO can effectively improve its lithium ion transmission. Here, we synthesized a LMO cathode material with a nanoscale crystal size using the flexible expanded graphite (EG) soft template and Pichini method. EG-controlled particle size and particle agglomeration of LMO is conducive to charge transfer and diffusion of lithium ions between LMO and the electrolyte, meanwhile, there are more redox sites on the nanosized LMO particles, which makes the redox reaction of LMO more thorough during the charge and discharge process, resulting in high capacitance performance. In order to obtain the considerably required lithium-ion capacitors (LICs) with high energy density and power density, we assembled aqueous LMO//activated carbon (AC) LICs with 5 M LiNO3 as the aqueous electrolytes, which are environmentally friendly, safe, low cost and have higher electrical conductivity than organic electrolytes. The optimal LIC has an energy density of 32.63 W h kg −1 at a power density of 500 W kg −1 and an energy density of 8.06 W h kg −1 at a power density of 10 000 W kg −1, which is higher than most of the LMO-based LICs in previous reports. After 2000 cycles, the specific capacitance retention rate was 75.9% at a current density of 3 A g −1 . Therefore, our aqueous LMO//AC LICs synthesized by the soft template/Pichini method have wide prospects and are suitable for low-cost, high-safety and high-power applications.